Tlingit carved raven rattle, Alaska, in engraving made 1837 - University of Washington Libraries
Photograph of engraving of carved wooden rattle in the shape of a raven Caption on image: Castanet Image from Edward Belcher's Narrative of a voyage round the world, 1843, v.1, p. 103